Diagnostic instruments for numeracy skills in chemistry learning: a development study Oriondo Antonio - Suwahono Suwahono; Fina Sa’adah; Yulianingsih Yulianingsih (EDUSAINS, 2025)
This study aims to develop a valid and reliable diagnostic instrument to measure students' numeracy skills in the context of chemistry learning. The instrument development followed a systematic procedure based on the Oriondo & Antonio model, which includes the stages of planning, construction, validation, and revision. The instrument was designed based on numeracy indicators integrated with chemistry content, particularly on topics requiring quantitative understanding, such as reaction rates. Content validity was reviewed by chemistry and education experts, while empirical reliability testing was conducted using Rasch modelling. The analysis results showed that the instrument had an Aiken validity of 0.80 (valid category), item reliability of 0.88 (very good category), person reliability of 0.80 (good category), and Cronbach's alpha value of 0.75 (good category). These findings indicate that the developed instrument meets the criteria for validity and reliability and is capable of specifically identifying students' misconceptions and numeracy gaps. Therefore, this instrument has the potential to be used as an initial diagnostic tool in designing remedial or enrichment learning strategies in chemistry classes